Priming the tennis player: a time-window framework for match-day and next-day neuromuscular preparation - Colomar, J.; Fernández-Fernández, J.; Carrera Prat, J.; Baiget, E. (Strength and Conditioning Journal, 2026)
Tennis tournaments impose fluctuating match times, consecutive-day play, and occasional same-day doubles, creating a need for preparation strategies that boost explosive performance while preserving freshness. This article integrates tennis-specific post-activation performance enhancement evidence with the broader priming literature to propose a practical, schedule-driven framework for neuromuscular preparation. Four time windows are outlined: (a) 2-3 hours "micro-priming" between matches, emphasizing minimal ballistic work, short accelerations, joint-specific isometrics and high-intent strokes to restore neural readiness; (b) 3-12 hours within-day priming under uncertain start times, using low-volume, high-intent strength-power exercises and sport-relevant sprints/throws while safeguarding against schedule compression; (c) 12-24 hours next-day (MD-1) priming, combining compact strength-power work with small doses of tennis-specific serving/rotational actions to leverage overnight recovery; and (d) 24-48 hours primers on rest days/cancellations, using low-volume maintenance strength-power sessions to preserve neuromuscular qualities. Across windows, recommended principles are low total volume, high movement intent, sport-relevant patterns and sufficient recovery, with strong emphasis on individualization (training status, strength level, accumulated fatigue, age, and sex). Key research gaps include ecologically valid tennis trials, dose-response profiling and studies in women and youth players.